Synergistic Effects of Ocean Background and Tropical Cyclone Characteristics on Tropical Cyclone-Induced Sea Surface Cooling in the Western North Pacific - Rao Rao; Chengcheng Yu; Peng Bai; Bo Li (Journal of Marine Science and Engineering)
Tropical cyclones (TCs) induce intense mixing in the upper ocean, which significantly impacts sea surface temperature (SST) and marine environment. Previous studies have shown that TCs can cause a decrease in sea surface temperature (DSST), while further research is required to elucidate the factors influencing SST changes. This study employs satellite observations and reanalysis data from the western North Pacific during 2002–2020 to investigate the relationship between DSST and the ocean background state (BG). In addition, by incorporating TC characteristics, we construct indices to explore the synergistic effects of TCs and BG on DSST, enabling a more comprehensive understanding of the mechanisms governing DSST variability. The results indicate that DSST exhibits significant monthly variations, with the maximum DSST in September for coastal regions and in August for offshore regions. Regardless of TC characteristics, when the mixed layer depth (MLD) exceeds 60 m or thermocline depth (TD) exceeds 115 m, it is difficult for the DSST to exceed 1 °C. In both coastal and offshore regions, MLD and TD exhibit moderate negative correlations with DSST, with values around −0.3. When TC characteristics are incorporated, these correlations rise to approximately 0.6, highlighting the importance of jointly considering BG and TC effects in characterizing DSST. The findings of this study provide theoretical support for improving the capability to predict DSST changes before the TC approaches the coast.